Newly synthesized mRNA escapes translational repression during the acute phase of the mammalian unfolded protein response. - Mohammed R Alzahrani; Bo-Jhih Guan; Leah L Zagore; Jing Wu; Chien-Wen Chen; Donny D Licatalosi; Kristian E Baker; Maria Hatzoglou (PLoS ONE, 2022)
Endoplasmic Reticulum (ER) stress, caused by the accumulation of misfolded proteins in the ER, elicits a homeostatic mechanism known as the Unfolded Protein Response (UPR). The UPR reprograms gene expression to promote adaptation to chronic ER stress. The UPR comprises an acute phase involving inhibition of bulk protein synthesis and a chronic phase of transcriptional induction coupled with the partial recovery of protein synthesis. However, the role of transcriptional regulation in the acute phase of the UPR is not well understood. Here we analyzed the fate of newly synthesized mRNA encoding the protective and homeostatic transcription factor X-box binding protein 1 (XBP1) during this acute phase. We have previously shown that global translational repression induced by the acute UPR was characterized by decreased translation and increased stability of XBP1 mRNA. We demonstrate here that this stabilization is independent of new transcription. In contrast, we show XBP1 mRNA newly synthesized during the acute phase accumulates with long poly(A) tails and escapes translational repression. Inhibition of newly synthesized RNA polyadenylation during the acute phase decreased cell survival with no effect in unstressed cells. Furthermore, during the chronic phase of the UPR, levels of XBP1 mRNA with long poly(A) tails decreased in a manner consistent with co-translational deadenylation. Finally, additional pro-survival, transcriptionally-induced mRNAs show similar regulation, supporting the broad significance of the pre-steady state UPR in translational control during ER stress. We conclude that the biphasic regulation of poly(A) tail length during the UPR represents a previously unrecognized pro-survival mechanism of mammalian gene regulation.